2019
DOI: 10.22361/jfmer/96267
|View full text |Cite
|
Sign up to set email alerts
|

Performance evaluation for hospital facility management: literature review and a research methodology

Abstract: Underpinning the quality of health services is a wide range of facilities services that require effective management. With the importance of such facilities management (FM) increasingly recognized, research on healthcare FM has grown, with many that attempted to develop some performance frameworks or key performance indicators (KPIs) for hospital FM. A credible scheme that is tailored for evaluating the holistic FM performance of hospital buildings, however, is yet to be seen. In order to establish such a perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, some of these presented KPIs are information rather than KPI, since they do not enable benchmarking by considering building characteristics such as site and location, appearance, etc. Lai and Yuen [35] identified 11 FM KPIs under four categories (physical, financial, environmental and health, safety and legal) for healthcare facilities with the usage of analytical network process (ANP) to identify the relative importance of KPIs by considering their impacts on each other. However, the study includes only literature review and research methodology.…”
Section: Background For Healthcare Facility Management Kpismentioning
confidence: 99%
See 1 more Smart Citation
“…However, some of these presented KPIs are information rather than KPI, since they do not enable benchmarking by considering building characteristics such as site and location, appearance, etc. Lai and Yuen [35] identified 11 FM KPIs under four categories (physical, financial, environmental and health, safety and legal) for healthcare facilities with the usage of analytical network process (ANP) to identify the relative importance of KPIs by considering their impacts on each other. However, the study includes only literature review and research methodology.…”
Section: Background For Healthcare Facility Management Kpismentioning
confidence: 99%
“…Shohet [38] identified 11 KPIs under asset development, organization and management, performance management, and maintenance efficiency for strategic healthcare FM and the identified parameters helped to benchmark them as inter-and intra-organizational. Lai and Yuen [35] investigated healthcare FM KPIs for Hong Kong that fell into six aspects: namely, safety, financial, physical, patient experience, environmental, and functional. In the study, 61 healthcare FM KPIs were found in a literature review.…”
Section: Background For Healthcare Facility Management Kpismentioning
confidence: 99%
“…As described in Lai and Yuen (2018), FM operational inputs determine the performance of facilities and hence the quality of facilities services to their end users. FM performance data may be collected through the following ways: solicitation of end user perceptions (e.g.…”
Section: Research Process and The Phase–hierarchy Modelmentioning
confidence: 99%
“…Along with the significant growth of services in the 21st century and globalization, the need to measure the performance, quality of service delivery, as well as their value position has even felt more (Tseng et al, 2015). Results obtained from effective performance evaluation are very important and make significant contributions to the growth, development and competitiveness in a wide range of industries (Mikolajczyk & Schmid, 2005;Lai & Yuen, 2019;Letina et al, 2020). In particular, in the field of the development or new services/ products, the discussion of performance evaluation has been of great interest, and there are many different definitions and perspectives on its research focus.…”
Section: Introductionmentioning
confidence: 99%